Accounting for environmental stress in restoration of intertidal foundation species. Issue 2 (7th December 2022) - Clausing, Rachel J.; De La Fuente, Gina; Falace, Annalisa; Chiantore, Mariachiara
Abstract: Restoration of foundation species in historical habitat may be difficult if adult facilitation is obligatory for survival of early life stages. On intertidal Mediterranean coasts, large‐scale loss of the dominant forest‐forming macroalga Ericaria amentacea have prompted restoration efforts using recruits. Yet, early life stages may be more susceptible to the abiotic stress that characterizes their habitat. We tested strategies to enhance resilience of lab‐cultured juveniles of E. amentacea to environmental stress in historical habitat lacking conspecifics. Juveniles were exposed in culture to fluctuations of the dominant physical stressors, irradiance and temperature, and then outplanted in upper and lower zones of their native intertidal range . Without adult canopy, juvenile outplant survival was limited to the lower tidal range, with nearly complete mortality in the upper zone. Survival was also strongly determined by spatial clumping of recruits within the outplant substrate. Longer‐term growth in the lower zone was enhanced by fluctuating mild stress in culture, with variable irradiance and concurrent heat pulses increasing post‐outplant cover by 40%–60% after 4 months. Clumping also promoted growth across experimental treatments. Synthesis and applications . Reliance on self‐facilitation feedbacks is a common barrier to foundation species restoration in high‐stress habitats. Our results suggest that without adult habitat amelioration, environmental stress limits recruit survival in intertidal algal forest. Yet, exposure to transient, low environmental stress in culture and outplanting of clumped individuals may confer resilience and allow successful establishment of early life stages in zones of reduced abiotic stress, providing a source for gradual colonization of more high‐stress areas. Abstract : Reliance on self‐facilitation feedbacks is a common barrier to foundation species restoration in high‐stress habitats. Our results suggest that without adult habitat amelioration, environmental stress limits recruit survival in intertidal algal forest. Yet, exposure to transient, low environmental stress in culture and outplanting of clumped individuals may confer resilience and allow successful establishment of early life stages in zones of reduced abiotic stress, providing a source for gradual colonization of more high‐stress areas.